Frontal sinus pneumocele caused by a maxillary sinus mucocele. Issue 4 (23rd April 2021) - Potamianos, Spyridon; Kanioura, Eftychia; Chrysovitsiotis, Georgios; Giotakis, Evangelos
Abstract : A sinus pneumocele is a rare entity caused by obstruction of a paranasal sinus ostium. It is characterised by dilation and expansion of the sinus, with subsequent bony erosion. The most probable mechanism is air trapping in the paranasal sinus, via a one-way valve mechanism. The case presented concerns a 68-year-old Caucasian man, with recurrent episodes of acute rhinosinusitis. Clinical examination and subsequent imaging of the face, revealed a large pneumocele of the right frontal sinus that significantly eroded the posterior sinus wall. A large mucocele of the right maxillary sinus was also noted, extending to the middle meatus, causing full obstruction of the ostiomeatal complex. Endoscopic sinus surgery was performed, the mucocele was removed and the pneumatisation pathway of the frontal sinus was restored. The patient reports full resolution of symptoms and shows no evidence of recurrence, 6 months postoperatively.